Artificial stone slab and preparation method thereof

By adding composite fine powder and resin improvers to the formula of artificial stone slabs, the problems of ultra-thin artificial stone slabs are solved, and high impact resistance and widespread application effects are achieved.

CN119528485APending Publication Date: 2025-02-28佛山市荣冠建材有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411502393.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing ultra-thin artificial quartz stone slabs are prone to breaking and have poor impact resistance, which limits their application range.

Method used

By adding composite fine powder and resin improver to the formula of artificial stone slabs, the fluidity of quartz sand and resin is improved, so that the components are distributed more tightly and uniformly, thereby improving cross-linking density and impact resistance, and increasing plasticity to prevent fracture.

Benefits of technology

It achieves the high impact resistance and non-breaking effect of ultra-thin artificial stone slabs, expands its application range, and has a thickness of less than 10mm, and is suitable for products such as translucent background walls, screens and craft lamp posts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102945060000081
    Figure BDA0005102945060000081
Patent Text Reader

Abstract

The invention relates to the technical field of artificial stone, in particular to an artificial stone slab and a preparation method thereof. The artificial stone plate is prepared from the following raw material components in parts by weight: 56 to 60 parts of quartz sand of 50 to 100 meshes, 24 to 30 parts of quartz sand of 400 to 500 meshes, 3 to 5 parts of composite fine powder of 800 to 850 meshes, 9 to 10.5 parts of resin, 0.8 to 1.2 parts of a resin modifier, 0.08 to 0.12 part of a curing agent and 0.08 to 0.12 part of a silane coupling agent. The artificial stone plate provided by the invention can be applied to preparation of ultrathin stone with the thickness of only 10mm, and still has good bending strength and impact strength, and the overall performance is equivalent to that of an artificial quartz stone plate with larger thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial stones, and in particular to an artificial stone slab and a preparation method thereof. Background Art

[0002] The thickness of existing artificial quartz slabs is generally 15mm to 30mm. Due to the thickness, the application scope of the product is relatively limited, and it can only be applied to dining and bathroom countertops and some floor paving. If the thickness of artificial quartz slabs can be reduced to less than 12mm, it can have a wider range of applications, such as making integrated cabinet doors and inlaid cabinet doors, decorative light boxes, and craft ceilings. At present, if the thickness of artificial quartz slabs is simply reduced without changing its original formula, the ultra-thin artificial quartz slabs produced will have problems such as easy breakage and poor impact resistance.

[0003] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an artificial stone slab and a preparation method thereof, aiming to solve the technical problems in the prior art that ultra-thin artificial quartz slabs are easy to break and have poor impact resistance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The first aspect of the present invention provides an artificial stone slab, wherein the raw materials for its preparation include the following components, measured by weight: 56 to 60 parts of quartz sand of 50 to 100 meshes, 24 to 30 parts of quartz sand of 400 to 500 meshes, 3 to 5 parts of composite fine powder of 800 to 850 meshes, 9 to 10.5 parts of resin, 0.8 to 1.2 parts of resin modifier, 0.08 to 0.12 parts of curing agent, and 0.08 to 0.12 parts of silane coupling agent.

[0007] The artificial stone slab, wherein the composite fine powder comprises talcum powder and amino-modified quartz powder.

[0008] The artificial stone slab, wherein the mass ratio of the talcum powder to the amino-modified quartz powder is 1:(1.5-2).

[0009] The artificial stone slab, wherein the resin comprises unsaturated polyester resin and epoxy resin.

[0010] The artificial stone board, wherein the mass ratio of the unsaturated polyester resin to the epoxy resin is (3-4):1.

[0011] The artificial stone slab, wherein the resin modifier includes at least one of vinyl bisstearamide, stearate, methyl styrene linear dimer, and trimesic acid.

[0012] The artificial stone board, wherein the resin modifier comprises vinyl bisstearamide and methyl styrene linear dimer.

[0013] The artificial stone slab, wherein the mass ratio of the vinyl bisstearamide to the methyl styrene linear dimer is 1:1.

[0014] The artificial stone slab comprises the following raw materials by weight: 58 parts of quartz sand with a mesh size of 50 to 100, 27 parts of quartz sand with a mesh size of 400 to 500, 4 parts of composite fine powder with a mesh size of 800 to 850, 9.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent.

[0015] The second aspect of the present invention provides a method for preparing an artificial stone slab, which is used to prepare the artificial stone slab as described above, comprising the following steps: mixing quartz sand of 50 to 100 meshes, quartz sand of 400 to 500 meshes, composite fine powder of 800 to 850 meshes, and a silane coupling agent, adding resin, resin modifier, and curing agent, pouring the mixture into a mold, and placing the mixture in a vacuum vibration press, vacuum degassing and vibrating and compacting the mixture, and after demolding, thermally curing and curing the mixture to obtain the artificial stone slab.

[0016] Beneficial effects: The present invention provides an artificial stone slab, wherein the artificial stone slab increases the fluidity of quartz sand and resin by adding composite fine powder and resin modifier into the formula, so that during the preparation process, each component can be more compact and distributed more evenly, thereby increasing the crosslinking density of the artificial stone slab and improving the impact resistance. In addition, the resin modifier can also increase the plasticity of the artificial stone slab, making the ultra-thin artificial stone slab less likely to break. The thickness of the artificial stone slab prepared by the formula of the present invention can reach less than 10 mm, and can be used to make products such as light-transmitting background walls, screens, and craft lamp posts, with a wider range of applications and economic value. DETAILED DESCRIPTION

[0017] The present invention provides an artificial stone board and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail in the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] The first aspect of the present invention provides an artificial stone slab, wherein the raw materials for its preparation include the following components, measured by weight: 56 to 60 parts of quartz sand of 50 to 100 meshes, 24 to 30 parts of quartz sand of 400 to 500 meshes, 3 to 5 parts of composite fine powder of 800 to 850 meshes, 9 to 10.5 parts of resin, 0.8 to 1.2 parts of resin modifier, 0.08 to 0.12 parts of curing agent, and 0.08 to 0.12 parts of silane coupling agent.

[0019] By mixing quartz sand of different specifications, a tighter structure can be formed by combining coarse and fine particles, thereby improving the density of the board. Among them, quartz sand of 50-100 mesh is used as aggregate, while quartz sand of 400-500 mesh and composite fine powder of 800-850 mesh are used as fillers to enhance the density of the board, making the antifouling effect better and the strength higher. Specifically, the composite fine powder of 800-850 mesh also mainly plays a lubricating role, which can make the quartz sand of 50-100 mesh and quartz sand of 400-500 mesh mixed more fully. Silane coupling agent can combine with the surface of quartz sand to form a uniform covering film, which can be connected with resin as a bridge connecting organic materials and inorganic materials. Resin modifier is used to improve the fluidity of resin, so that the mixing between organic materials and inorganic materials is more uniform. Resin modifier can also improve the plasticity of artificial stone board, making it not easy to break.

[0020] Preferably, the composite fine powder includes talcum powder and amino-modified quartz powder. Talc powder has good lubricity and slip-promoting properties, and in addition to promoting the mixing of coarse particles, it can also play a good filling role.

[0021] Preferably, the mass ratio of the talcum powder to the amino-modified quartz powder is 1:(1.5-2).

[0022] Preferably, the resin includes unsaturated polyester resin and epoxy resin. The epoxy group in the epoxy resin can react with the amino group on the surface of the amino-modified quartz powder to increase the cross-linking density and cross-linking strength. In addition, the epoxy resin can increase the hardness of the stone slab and increase the wear resistance. The unsaturated polyester resin has high strength and toughness and can withstand large external forces without being easily damaged. In addition, the unsaturated polyester resin also has good transparency. When making ultra-thin artificial stone slabs, the stone slabs can have a transparent effect. The combined use of unsaturated polyester resin and epoxy resin can form a variety of cross-linking structures, making the connection tighter and the cross-linking density greater.

[0023] Preferably, the mass ratio of the unsaturated polyester resin to the epoxy resin is (3-4):1.

[0024] Preferably, the resin modifier includes at least one of vinyl bisstearamide, stearate, methyl styrene linear dimer, and trimesic acid.

[0025] Vinyl bisstearamide can be used as an internal and external lubricant to improve the heat resistance, weather resistance and fluidity of polyester. Methyl styrene linear dimer can improve the rheological properties of the resin and reduce the melt viscosity, and participate in cross-linking. Methyl styrene linear dimer can also be used as an anti-crack additive to overcome the cracks formed during the molding of artificial stone slabs, and the artificial stone slabs manufactured thereby have good transparency, crack resistance, hot water resistance and heat resistance. Trimellitic acid can be used as a branching agent to improve the fluidity of the resin.

[0026] Preferably, the resin modifier includes vinyl bis stearamide and methyl styrene linear dimer. Vinyl bis stearamide and methyl styrene linear dimer improve the fluidity of the resin through different mechanisms, which can make the improvement effect better, and the joint use of the two can increase the overall performance of the artificial stone board.

[0027] Preferably, the mass ratio of the vinyl bisstearamide to the methyl styrene linear dimer is 1:1.

[0028] Preferably, the raw materials for preparing the artificial stone slab include the following components, measured by weight: 58 parts of quartz sand of 50-100 mesh, 27 parts of quartz sand of 400-500 mesh, 4 parts of composite fine powder of 800-850 mesh, 9.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent.

[0029] The second aspect of the present invention provides a method for preparing an artificial stone slab, which is used to prepare the artificial stone slab as described above, comprising the following steps: mixing quartz sand of 50 to 100 meshes, quartz sand of 400 to 500 meshes, composite fine powder of 800 to 850 meshes, and a silane coupling agent, adding resin, resin modifier, and curing agent, pouring the mixture into a mold, and placing the mixture in a vacuum vibration press, vacuum degassing and vibrating and compacting the mixture, and after demolding, thermally curing and curing the mixture to obtain the artificial stone slab.

[0030] The present invention is further described below with reference to specific examples and comparative examples.

[0031] Example 1

[0032] An artificial stone board, wherein the raw materials for its preparation include the following components by weight: 58 parts of 100-mesh quartz sand, 27 parts of 500-mesh quartz sand, 4 parts of 800-mesh composite fine powder, 9.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent;

[0033] Wherein, the composite fine powder is composed of talcum powder and amino-modified quartz powder, and the mass ratio of talcum powder to amino-modified quartz powder is 1:1.5;

[0034] The resin is composed of unsaturated polyester resin and epoxy resin, and the mass ratio of the unsaturated polyester resin to the epoxy resin is 3.5:1;

[0035] The resin modifier is composed of vinyl bisstearamide and methyl styrene linear dimer, and the mass ratio of vinyl bisstearamide to methyl styrene linear dimer is 1:1;

[0036] The preparation method of the artificial stone slab comprises the following steps:

[0037] Mix 100-mesh quartz sand, 500-mesh quartz sand, 800-mesh composite fine powder, and silane coupling agent, add resin, resin modifier, and curing agent, pour into a 10 mm artificial stone plate mold, and put it into a vacuum vibration press for vacuum degassing and vibration compaction. After demolding, the material is thermally cured and cured to obtain a 10 mm thick artificial stone plate.

[0038] Example 2

[0039] An artificial stone slab, the raw material used in its preparation is different from that in Example 1 in that the composite fine powder is amino-modified quartz powder.

[0040] Example 3

[0041] An artificial stone slab, the raw materials used in its preparation are different from those in Example 1 in that the composite fine powder consists of talcum powder and amino-modified quartz powder, and the mass ratio of the talcum powder to the amino-modified quartz powder is 1:0.5.

[0042] Example 4

[0043] An artificial stone board, the raw material used in its preparation is different from that in Example 1 in that the resin is an unsaturated polyester resin.

[0044] Example 5

[0045] An artificial stone board, the raw materials used in its preparation are different from those in Example 1 in that the resin consists of unsaturated polyester resin and epoxy resin, and the mass ratio of the unsaturated polyester resin to the epoxy resin is 2:1.

[0046] Example 6

[0047] An artificial stone board, the raw materials used in its preparation are different from those in Example 1 in that the resin modifier is vinyl bisstearamide.

[0048] Example 7

[0049] An artificial stone board, the raw materials used in its preparation are different from those in Example 1 in that the resin modifier is a linear dimer of methyl styrene.

[0050] Example 8

[0051] An artificial stone board, wherein the raw materials for its preparation include the following components by weight: 57.3 parts of 100-mesh quartz sand, 27 parts of 500-mesh quartz sand, 4 parts of 800-mesh composite fine powder, 10.5 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent;

[0052] Wherein, the composite fine powder is composed of talcum powder and amino-modified quartz powder, and the mass ratio of talcum powder to amino-modified quartz powder is 1:1.5;

[0053] The resin is composed of unsaturated polyester resin and epoxy resin, and the mass ratio of the unsaturated polyester resin to the epoxy resin is 3.5:1;

[0054] The resin modifier consists of vinyl bisstearamide and methyl styrene linear dimer, and the mass ratio of vinyl bisstearamide to methyl styrene linear dimer is 1:1.

[0055] Comparative Example 1

[0056] An artificial stone board, wherein the raw materials for its preparation include the following components by weight: 54 parts of 100-mesh quartz sand, 27 parts of 500-mesh quartz sand, 4 parts of 800-mesh composite fine powder, 13.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent;

[0057] Wherein, the composite fine powder is composed of talcum powder and amino-modified quartz powder, and the mass ratio of talcum powder to amino-modified quartz powder is 1:1.5;

[0058] The resin is composed of unsaturated polyester resin and epoxy resin, and the mass ratio of the unsaturated polyester resin to the epoxy resin is 3.5:1;

[0059] The resin modifier consists of vinyl bisstearamide and methyl styrene linear dimer, and the mass ratio of vinyl bisstearamide to methyl styrene linear dimer is 1:1.

[0060] Comparative Example 2

[0061] An artificial stone board, wherein the raw materials for its preparation include the following components by weight: 62 parts of 100-mesh quartz sand, 27 parts of 500-mesh quartz sand, 4 parts of 800-mesh composite fine powder, 5.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent;

[0062] Wherein, the composite fine powder is composed of talcum powder and amino-modified quartz powder, and the mass ratio of talcum powder to amino-modified quartz powder is 1:1.5;

[0063] The resin is composed of unsaturated polyester resin and epoxy resin, and the mass ratio of the unsaturated polyester resin to the epoxy resin is 3.5:1;

[0064] The resin modifier consists of vinyl bisstearamide and methyl styrene linear dimer, and the mass ratio of vinyl bisstearamide to methyl styrene linear dimer is 1:1.

[0065] Comparative Example 3

[0066] An artificial stone board, wherein the raw materials for its preparation include the following components by weight: 62 parts of 100-mesh quartz sand, 23 parts of 500-mesh quartz sand, 4 parts of 800-mesh composite fine powder, 9.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent;

[0067] Wherein, the composite fine powder is composed of talcum powder and amino-modified quartz powder, and the mass ratio of talcum powder to amino-modified quartz powder is 1:1.5;

[0068] The resin is composed of unsaturated polyester resin and epoxy resin, and the mass ratio of the unsaturated polyester resin to the epoxy resin is 3.5:1;

[0069] The resin modifier consists of vinyl bisstearamide and methyl styrene linear dimer, and the mass ratio of vinyl bisstearamide to methyl styrene linear dimer is 1:1.

[0070] Comparative Example 4

[0071] An artificial stone board comprises the following raw materials by weight: 60 parts of 100-mesh quartz sand, 30 parts of 500-mesh quartz sand, 9.8 parts of unsaturated polyester resin, 0.1 parts of curing agent and 0.1 parts of silane coupling agent.

[0072] The preparation methods of the artificial stone slabs in the above embodiments and comparative examples are the same as that in embodiment 1.

[0073] The bending strength and impact strength of the artificial stone slabs obtained in the above embodiments and comparative examples were tested with reference to GB / T 2567-2008.

[0074] Refer to GBT 41919-2022 to test the hardness and wear resistance of artificial stone slabs.

[0075] The corresponding test results are shown in the following table:

[0076]

[0077] From the above results, it can be seen that after Examples 1-8 of the present invention are prepared into ultra-thin stone slabs with a thickness of only 10 mm, their bending strength, impact strength, Mohs hardness and wear resistance all meet the test standards, and their comprehensive performance is comparable to that of current artificial stone slabs with a thickness of more than 15 mm.

[0078] Further comparison of Examples 1-8 shows that the comprehensive performance of the artificial stone slab prepared in Example 1 is the best. Compared with Example 1, Example 2 does not use talcum powder, and its bending strength and impact strength are both lower than those of Example 1, indicating that the use of talcum powder can further promote the compactness of the artificial stone slab.

[0079] Compared with Example 1, Example 3 uses more talcum powder, but its comprehensive performance is not as good as Example 1. It can be seen from the data that excessive use of talcum powder will lead to a decrease in the wear resistance and hardness of the artificial stone slab. This is because the hardness of talc is very low. Although it can play a good lubricating role, it is not advisable to use too much.

[0080] Compared with Example 1, Example 4 does not use epoxy resin. From the performance of the artificial stone board, its overall performance is reduced. The reason is that without epoxy resin, the types of cross-linked structures that can be formed by the artificial stone board will be reduced, and the cross-linking density will be significantly reduced.

[0081] In Example 5, compared with Example 1, the amount of epoxy resin used is greater. From the results, the bending strength of the artificial stone board decreases significantly, which may be due to the fact that the plasticity of epoxy resin is not as good as that of unsaturated polyester resin.

[0082] Compared with Example 1, Example 6 and Example 7 use only vinyl bisstearamide and methyl styrene linear dimer as resin modifiers, respectively. The comprehensive performance of Example 6 and Example 7 is not as good as that of Example 1, indicating that the compound use of vinyl bisstearamide and methyl styrene linear dimer can further improve the performance of artificial stone slabs.

[0083] Compared with Example 1, Example 8 has different amounts of quartz sand and resin, and the overall performance of Example 8 is slightly reduced, but is generally equivalent.

[0084] Compared with Example 1, the amount of resin used in Comparative Example 1 is larger and exceeds the protection scope of the present invention. From the test results, the test values ​​of wear resistance, hardness and impact strength of Comparative Example 1 are significantly reduced.

[0085] Compared with Example 1, Comparative Example 2 uses more 100-mesh quartz sand and less resin. From the test results, the values ​​of the bending strength and Mohs hardness of the artificial stone slab in Comparative Example 2 are significantly reduced. The reason may be that the amount of resin is insufficient, resulting in insufficient cross-linking strength and reduced plasticity of the stone slab. In addition, when the amount of 100-mesh quartz sand is large, it will also affect the ratio of coarse particles and fine particles, resulting in a decrease in the overall filling rate and a decrease in compactness.

[0086] Compared with Example 1, in Comparative Example 3, more 100-mesh quartz sand is used, while less 500-mesh quartz sand is used. At this time, the ratio of coarse particles and fine particles is obviously unbalanced compared with Example 1, which will lead to increased gaps and low compactness, thus affecting the overall performance.

[0087] Comparative Example 4 is a formula for preparing artificial stone slabs with a thickness of 15 mm or more in the prior art. The bending strength and impact strength of the 20 mm artificial stone slab prepared by this formula are equivalent to those of Example 1. However, when used to prepare 10 mm artificial stone slabs, it can be seen from the test results that the bending strength and impact strength values ​​are significantly reduced and are easy to break.

[0088] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.

Claims

1. An artificial stone slab, characterized in that: The raw materials for its preparation include the following components by weight: 56-60 parts of quartz sand with a mesh size of 50-100, 24-30 parts of quartz sand with a mesh size of 400-500, 3-5 parts of composite fine powder with a mesh size of 800-850, 9-10.5 parts of resin, 0.8-1.2 parts of resin improver, 0.08-0.12 parts of curing agent and 0.08-0.12 parts of silane coupling agent.

2. The artificial stone slab according to claim 1, characterized in that: The composite fine powder comprises talcum powder and amino-modified quartz powder.

3. The artificial stone slab according to claim 2, characterized in that: The mass ratio of the talc powder to the amino-modified quartz powder is 1:(1.5-2).

4. The artificial stone slab according to claim 3, characterized in that: The resin includes unsaturated polyester resin and epoxy resin.

5. The artificial stone slab according to claim 4, characterized in that: The mass ratio of the unsaturated polyester resin to the epoxy resin is (3-4):

1.

6. The artificial stone slab according to claim 1, characterized in that: The resin modifier includes at least one of vinyl bisstearamide, stearate, methyl styrene linear dimer, and trimesic acid.

7. The artificial stone board according to claim 6, characterized in that: The resin modifier includes vinyl bisstearamide and methyl styrene linear dimer.

8. The artificial stone slab according to claim 7, characterized in that: The mass ratio of the vinyl bisstearamide to the methyl styrene linear dimer is 1:

1.

9. The artificial stone slab according to claim 1, characterized in that: The raw materials for its preparation include the following components by weight: 58 parts of quartz sand with a mesh size of 50 to 100, 27 parts of quartz sand with a mesh size of 400 to 500, 4 parts of composite fine powder with a mesh size of 800 to 850, 9.8 parts of resin, 1 part of resin modifier, 0.1 part of curing agent, and 0.1 part of silane coupling agent.

10. A method for preparing an artificial stone slab, characterized in that: The method for preparing the artificial stone slab according to any one of claims 1 to 9 comprises the following steps: Mix 50-100 mesh quartz sand, 400-500 mesh quartz sand, 800-850 mesh composite fine powder and silane coupling agent, add resin, resin modifier and curing agent, pour into a mold, put into a vacuum vibration press, vacuum degassing and vibration compaction, and after demolding, heat cure and curing the material to obtain the artificial stone slab.